2007
DOI: 10.1159/000104443
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension and Erythropoietin

Abstract: Numerous uremic patients on hemodialysis have pulmonary hypertension attributable to the presence of arteriovenous fistulas, vascular calcification, and endothelial dysfunction due to alterations in the balance between vasoconstrictive and vasodilatory substances. For these reasons, the effects of recombinant human erythropoietin, a drug widely used in patients on dialysis, on the pulmonary circulation were studied. Some authors maintain that recombinant human erythropoietin has an antihypertensive effect, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
(37 reference statements)
2
26
0
Order By: Relevance
“…22,23 In a study of 124 adults with sickle cell disease, no relationship between erythropoietin and pulmonary hypertension was detected. 24 We, however, observed that serum erythropoietin concentration is associated with higher tricuspid regurgitation velocity in sickle cell disease patients even after adjustment for the degree of hemolysis and other significant covariates, providing evidence for the concept that erythropoietin may be related to the development of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In a study of 124 adults with sickle cell disease, no relationship between erythropoietin and pulmonary hypertension was detected. 24 We, however, observed that serum erythropoietin concentration is associated with higher tricuspid regurgitation velocity in sickle cell disease patients even after adjustment for the degree of hemolysis and other significant covariates, providing evidence for the concept that erythropoietin may be related to the development of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PH ranges from 9-39% in predialysis patients with stage-5 CKD (Yigla et al, 2003;Buemi et al, 2007;Havlucu et al, 2007;Abdelwhab and Elshinnawy, 2008;Issa et al, 2008), 18.8-68.8% in hemodialysis patients, and 0-42% in individuals on peritoneal dialysis therapy (Kumbar et al, 2007;Bozbas et al, 2009;Unal et al, 2009;Casas-Aparicio et al, 2010;Kiykim et al, 2010;Fabbian et al, 2011;Agarwal, 2012;Etemadi et al, 2012). In our study, 37 of 128 (28.91%) CKD patients from China, who accepted no dialysis or renal transplantation, had Doppler-derived PASP ≥ 35 mmHg.…”
Section: Discussionmentioning
confidence: 55%
“…Varied cutoffs of PH have been adopted in studies, ranging from 25 to ≥45 mmHg (Yigla et al, 2009;Kiykim et al, 2010), which result in different conclusions about PH prevalence. Here, we adopted the PH diagnostic criteria as a PASP ≥ 35 mmHg (Buemi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uremia (leading to pulmonary arterial vasoconstriction), the presence of an AVF, low bioavailability of nitric oxide (17), an elevated endothelin level (18,19), vascular calcification, hypervolemia, exposure to dialysis membranes, endothelial dysfunction, and anemia (20,21) are the reported pathogenetic mechanisms for the development of PHT in patients with CKD. Patients with an AVF had a high incidence of PHT due to increased cardiac output and it has been reported that the incidence of PHT in stage 5 CKD patients with an AVF was 40-50% (12,22).…”
Section: Discussionmentioning
confidence: 99%